The Potray of the Main Characters in the Complete Works of O. Henry - Muhammad Hasby Ash-shiddiqy; Muhammad Natsir; Anjar Dwi Astuti (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2020)
This study aims to determine the depiction of the main character and also how the author describes the main characters in O. Henry's short stories collection. The method in this study is qualitative by using library research, the data for the research is all sentences and dialogues among the characters in the short story which are related to the characters' characterization. The steps to collect the data are: a) Reading the five title short stories of The Complete Works of O. Henry, b) Taking notes, the required expressions or sentences from the short story that contain the information about main characters., c) Identifying all sentences and dialogues in the short story to get the data, d) Choosing the data dealing with the problems that will be investigated, the writer used a content analysis method as the data analysis. The findings of this study reveal that In the five short story titles in the collection of short stories